PENGARUH GAJI, TUNJANGAN, DAN PROMOSI JABATAN TERHADAP KINERJA PEGAWAI (Studi pada Badan Kepegawaian Daerah Provinsi Jawa Tengah) - Vahdist, Riski; Mahfudz, Mahfudz (Faculty of Economics and Business Diponegoro University, 2017)
Good performance of employee in organization is important thing in running an organization. The better performance of employee could make a greater opportunity to achieve organization goal. To improve the performance of employee, organization should arrange some strategies which is effective and efficient in order to achieve the better result. This study aims to analyze the effect of salary, allowance, and job promotion to employee performance in Badan Kepegawaian Daerah, Center of Java Province, this study involve 103 respondents as the sample.Â The selection of sample was conducted through sensus method. The variable used in this study were salary, allowance, job promotion, and employee performance. Statistic analysis method was conducted by multiple regresive linear technique with SPSS version 23.The result of this study shows that there is signficant effect of salary, allowance, and job promotion to employee performance simultaneously. Whereas partially salary, allowance, and job promotion have positive and significant effectt to employee performance. Employee performance is affected 42.6% by those three variables.